International security and peacebuilding Africa, the Middle East, and Europe - Bah, Abu Bakarr 1969- (Indiana University Press, 2017)
Together the essays provide a theoretical and empirical critique of global liberal governance and, as they note challenges to regional and international cooperation, they reveal that global liberal governance may threaten fragile governments and endanger human security at all levels